Da’wa Message on Net TV's Muslim Travelers Program - Prihananto, Prihananto; Mawaddah, Isdiadatul; Maesaroh, Imas (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
Da’wa is growing with the existence of communication media that continues to progress. Da’wa messages are increasingly diverse and packaged. Like the Muslim Travelers NET TV program, which is a traveling program that presents da’wa messages and is packaged according to the millennial generation. Therefore, in this study, we examine the message of da’wa on the Spanish edition of the Muslim Travelers NET TV program and the dominant message of da’wa. The method in this study uses descriptive quantitative content analysis to describe in detail a message. Using the thematic unit of analysis, based on the theme of the message of da’wa. Sources and types of data use videos of Muslim travelers traveling to Spain which consist of three videos. Using observation data collection techniques, direct observation of research objects and documentation, the data is then transcribed into primary data. After the data was collected, it was analyzed using SPSS version 16 for Windows. From the results of the analysis, it can be concluded that the Spanish Travel Program Muslim Travelers NET TV program contains three elements of the message of preaching aqidah, morals and shari'ah. The message of faith is illustrated by an invitation to maintain faith, and show confidence, with a percentage of 34.3%. Moral messages show examples of behaving towards fellow humans with a percentage of 34.3%. And the Shari'ah message provides an example of how a Muslim implements Islamic Shari'ah in Spain with a percentage of 31.5%. This study only examines the message of the da’wa contained, further researchers can examine more deeply about the program.